2019
DOI: 10.1371/journal.pone.0214238
|View full text |Cite
|
Sign up to set email alerts
|

Tensor-valued diffusion encoding for diffusional variance decomposition (DIVIDE): Technical feasibility in clinical MRI systems

Abstract: Microstructure imaging techniques based on tensor-valued diffusion encoding have gained popularity within the MRI research community. Unlike conventional diffusion encoding—applied along a single direction in each shot—tensor-valued encoding employs diffusion encoding along multiple directions within a single preparation of the signal. The benefit is that such encoding may probe tissue features that are not accessible by conventional encoding. For example, diffusional variance decomposition (DIVIDE) takes adva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 83 publications
(140 citation statements)
references
References 96 publications
(198 reference statements)
6
134
0
Order By: Relevance
“…As expected, the differences in MD and FA were relatively small (see Supporting Information Figure ), but gross parameter differences were observed in the µFA, MK A (overestimated by 0.3 and 0.8, respectively), and MK I (underestimated by 0.8). The underestimation of MK I was severe enough to cause large regions in the parenchyma to exhibit negative values, which are not expected from the current experiments . The measured and predicted differences show a remarkable similarity, indicating that the difference between signal and QTI parameters based on DDE‐PTE and MCW‐PTE is indeed primarily because of the prominent concomitant gradients created by DDE‐PTE.…”
Section: Resultssupporting
confidence: 57%
“…As expected, the differences in MD and FA were relatively small (see Supporting Information Figure ), but gross parameter differences were observed in the µFA, MK A (overestimated by 0.3 and 0.8, respectively), and MK I (underestimated by 0.8). The underestimation of MK I was severe enough to cause large regions in the parenchyma to exhibit negative values, which are not expected from the current experiments . The measured and predicted differences show a remarkable similarity, indicating that the difference between signal and QTI parameters based on DDE‐PTE and MCW‐PTE is indeed primarily because of the prominent concomitant gradients created by DDE‐PTE.…”
Section: Resultssupporting
confidence: 57%
“…The number of encoding directions was chosen such that a rotation invariant powder signal could be obtained with the acquisition protocol. The minimum number of directions necessary to fulfil this requirement was estimated by following a previously proposed simulation framework . Most renal DTI studies have found FA in the renal medulla to be (1) lower than 0.5, and (2) higher than cortical FA (see above).…”
Section: Methodsmentioning
confidence: 99%
“…Most renal DTI studies have found FA in the renal medulla to be (1) lower than 0.5, and (2) higher than cortical FA (see above). Therefore, assuming a maximum FA of 0.5 (see Results for details of our FA estimates in this data set), ~11 directions yield a rotation invariant powder signal for b × MD < 3, where MD = mean diffusivity. As such, considering the highest b‐value used in this study (1000 s/mm 2 ), ~11 directions yield a rotation invariant powder signal for a MD of 3 × 10 −3 mm 2 /s (diffusion coefficient of water at body temperature), which is above the typically observed MD in the renal cortex and medulla (also verified in our data, see Results).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The techniques for data analysis described in this section were employed after arithmetic averaging of the signal across diffusion‐encoding directions, so‐called “powder averaging” (Callaghan, Jolley, & Lelievre, ; Jespersen, Lundell, Sønderby, & Dyrby, ; Lasič et al, ). Provided data is acquired with a sufficient number of directions (Szczepankiewicz, Westin, Ståhlberg, Lätt, & Nilsson, ), powder averaging yields a signal whose orientation‐invariant aspects of diffusion are preserved but with an orientation distribution that mimics complete dispersion of anisotropic structures.…”
Section: Theorymentioning
confidence: 99%